Fundementals of Enzymology The Cell And Molecular Biology of Catalytic Proteins - Price, Nicholas C Stevens, Lewis (OXFORD University Press, 1999)
Enzymes are biological catalysts that have a number of remarkable properties. Fundamentals of Enzymology, 3rd ed builds on the strengths of the previous two editions to show how we can understand these properties and explain how enzymes work in cells and organisms and how they can be clinically and commercially exploited